Proteomics studies reveal important information on small molecule therapeutics: a case study on plasma proteins - Zolla, Lello (Drug Discov Today, 2008)
The most abundant proteins in serum, such as albumin and IgG, act as molecular sponges that bind and transport low molecular weight proteins/peptides and drugs. In the near future, pharmacoproteomics, the use of proteomic technologies in the field of drug discovery and development, and interactomics, the branch of proteomics which is concerned with identifying interactions between proteins, will allow researchers to (i) know the specific protein changes that occur in biological compartments in response to drug administration; (ii) design small novel therapeutic molecules that can have extended half-lives if carried by plasma protein in the blood stream. Advances in these fields will open new avenues of tailor-made molecular therapy, reducing present limitations on treatment arising from toxicity and inefficiency. In this short review we report and discuss the most recent developments arising from the use of proteomic tools in blood plasma protein research, looking at the identification of proteins found in plasma as well as their interactions with small molecules such as drugs, peptides, organic chemicals and metals. We believe this research demonstrates that proteomic technologies, and in particular pharmacoproteomics, interactomics and post-translational modification analysis, could be instrumental in the design of new tailor-made drugs leading to substantial improvements in molecular therapy.